Sosialisasi buku panduan peguatan proyek Profil Pelajar Pancasila di SDN Sangkanhurip Kecamatan Sangkanhurip Kabupaten Kuningan - Febby Fajar Nugraha; Mia Zultrianti Sari; Agus Gunawan (IKIP SILIWANGI, 2023)
The implementation of the independent curriculum is still taboo for some schools, because it turns out that in its implementation there are still many teachers who are still confused and feel difficulties. When viewed from its implementation, the project to strengthen the Pancasila profile is the main focus in implementing the independent learning curriculum, but the problem is that the implementation of the curriculum has not been implemented optimally and evenly, because not all schools have implemented the curriculum, especially in practice the independent learning curriculum is only applied at the elementary level. elementary school grades 1 and 4. The purpose of this activity program is to provide training and mentoring for teachers in strengthening the implementation of strengthening the Pancasila profile project. The method used in Community Service is through the approach of workshops, lectures, questions and answers and mentoring of the socialization guidebook for strengthening the Pancasila profile project. This community service activity can provide direct benefits to partners in increasing understanding and skills related to implementation activities for strengthening student profile projects Pancasila, an indicator of the success of service activities is marked by the enthusiasm of the teachers in participating in training activities